Displacement and Belonging: the Search for Refuge in When Rain Clouds Gather - Youssouf DIARRASSOUBA (Akofena)
Abstract: This article examines the theme of migration and the search for refuge in Bessie Head's novel When Rain Clouds Gather, focusing on the experiences of displacement and the challenges of belonging faced by the protagonist, Makhaya, and other characters. Set in the socio-political context of apartheid-era Southern Africa, the novel portrays the transformative journey of individuals seeking refuge in Botswana, escaping political violence, and striving for self-discovery. By analyzing the internal and external conflicts that shape the characters' paths, this paper explores how exile functions not only as a means of survival but also as a space for personal growth and the formation of new identities. The article further investigates the dynamics of community building in a foreign land, highlighting the tension between isolation and solidarity, as well as the complex process of adapting to unfamiliar environments. Through the lens of migration theory, the study addresses the broader implications of displacement, the search for home, and the possibility of renewal, ultimately reflecting on the profound impact of migration on both individual lives and collective societal structures. The paper concludes by reflecting on how migration in When Rain Clouds Gather represents a journey of reconciliation, healing, and hope for the future.